(3eHGMKGJ GHf SjfG eY JdejPg HgefjGQ Hf eQRHGfs - (3HgefjGQ Hf eQRjGfs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3S eG eYfi GdYbd HGdbhI aEf GdTF GdPi jOQc efG GdeYbhdGJ bO HGf s
(3BNQgG (B:s
(3hjYfi HGdeDjO GdPGJ heG HGdPGJ hef gPG GdbOQ dG jdRe ZjQ gPG GdbOQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG (B(150 x) s
Keywords: (3GdadSaI hGdefWbs